Bioenergy and biofertilizer recovery from organic fraction of municipal solid waste for environmental protection and sustainable economy in Liaoning province, China - Yang, Le (2021)

(untitled)
As time goes on, the rapid increase of global municipal solid waste production has aroused people's attention to the environmental impacts such as gas emissions, landfill problems and water quality deterioration. In China, 90% of solid waste is disposed of in landfills and incineration, and China has a low level of awareness of recycling actions, which reminds the importance of good management of land use waste disposal. Among many types of municipal solid waste, organic waste is still the most concerned type. This study focuses on the conversion of organic waste in to bio gas and biological fertilizer to replace the traditional landfill and to support incineration treatment methods, which has a great potential to contribute to the economic cycle. Biogas is a clean energy and pollution-free emission, the sustainability and environmental impact of biogas production and organic of municipal solid waste (OFMSW) anaerobic digestion fertilizer recovery were evaluated. In order to evaluate the economic benefit and return on investment (ROI), the organic part of municipal solid waste was characterized through research and investigation, and the economic benefit evaluation was calculated. The research analysis provided includes the municipal solid Liaoning Province. The project resulted in producing clean electricity reducing the square value meters per day of land use, avoiding leachate production and treatment, production of biological fertilizer. In terms of economic benefits, electricity sales help to realize daily electricity sales through the feed in tariff (FIT), and also help to save RMB - selling biological fertilizer and daily landfill operation. In the initial capital expenditure (CAPEX) and operating expenditure (OPEX) of the biogas power plant are RMB 9103.281 million and RMB 1517.213 million / year respectively, and the OFMSW treatment fee is RMB 5.554 million / day, the ROI is 5.1 year